Dual Predictors of Teacher Performance in Madrasah Tsanawiyah: The Roles of Instructional Effectiveness and Professional Competence - Mamat Rahmatullah; Maranda Sukma Mufatzizah (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
Teacher performance in Islamic secondary schools (Madrasah Tsanawiyah) in Indonesia remains a concern for policymakers, with instructional quality and professional competence frequently cited as key determinants. This study examined the individual and combined predictive contributions of instructional effectiveness and teacher competence to teacher performance among Madrasah Tsanawiyah teachers in Serang, Banten, Indonesia. A quantitative correlational design was employed with a sample of 100 teachers selected through proportional random sampling from public Madrasah Tsanawiyah in the region. Data were collected via structured Likert-scale questionnaires and analyzed using Pearson product-moment correlation, simple linear regression, and multiple regression analysis, preceded by Kolmogorov–Smirnov normality testing. Results showed that instructional effectiveness (r = .672, R² = .452) and teacher competence (r = .718, R² = .516) each demonstrated significant positive correlations with teacher performance. When examined simultaneously, the two predictors collectively explained 61.5% of the variance in teacher performance (R = .784, p < .001). These findings indicate that neither instructional effectiveness nor teacher competence alone is sufficient to maximize performance; their synergistic development is essential. The study provides empirical evidence for integrated teacher professional development policies in Islamic secondary education in Indonesia.